Law enforcement personnel are willing to change, but report influencing beliefs and barriers to optimised dietary intake - Kristen MacKenzie-Shalders; Charlene Matthews; Joe Dulla; Robin Orr (BMC, 2020)
Abstract Bacmround Law enforcement personnel have been recognized as having a high risk for several lifestyle-related health conditions which, in combination with the nature of their work (sedentary roles interspersed with intermittent high-intensity activity, shift work, and a high stress-load), can have a negative impact on their health. The aim of this study was to investigate the dietary habits and factors or barriers influencing these habits within a cohort of law enforcement personnel in the United States of America. Method Cross-sectional data were obtained via validated paper-based surveys being the Perceived Barriers to Healthy Eating, Food Choice Questionnaire and Rapid Eating Assessment for Participants, Short Version. Results A total of 159 participants (median age = 27 [range 19-60] years; 74% males) participated. Barriers to healthy eating included being busy and irregular working hours. Overall, 91% (n = 143) placed high importance on consuming nutritious food and 80% (n = 126) on food high in vitamins and minerals. A further 80% (n = 127) emphasized high protein content and 41% (n = 62) followed a high protein diet. Barriers to healthy eating included busy lifestyle (60%, n = 94), and irregular working hours (41%, n = 64). Overall, 80% (n = 127) were very willing to make changes in eating habits to be healthier. Conclusion Law enforcement officers know what they should eat and report convenience and health the most important factors guiding their food choices. Knowing this, officers find challenges putting good dietary practices into practice due to factors like a busy lifestyle and irregular work hours. Reportedly "very willing" to make changes in their eating habits to be healthier, future interventions should focus on how to effect changes to their eating habits as opposed to focussing on what to eat.